When is a mutation not a mutation: the case of the c.594-2A>C splice variant in a woman harbouring another BRCA1 mutation in trans. Issue 1 (December 2016) - Wong-Brown, Michelle; McPhillips, Mary; Gleeson, Margaret; Spigelman, Allan; Meldrum, Cliff; Dooley, Susan; Scott, Rodney
Abstract Since the identification ofBRCA1 there has only ever been described two bi-allelic mutation carriers, one of whom was subsequently shown to be a mono-allelic carrier. The second patient diagnosed with two BRCA1 mutations appears to be accurate but there remain some questions about the missense variant identified in that patient. In this report we have identified a woman who is a bi-allelic mutation carrier of BRCA1 and provide an explanation as to why this patient has a phenotype very similar to that of any mono-allelic mutation carrier. The splice variant identified in this patient appears to be associated with the up-regulation of a BRCA1 splice variant that rescues the lethality of being a double mutant. The consequences of the findings of this report may have implications for mutation interpretation and that could serve as a model for not only BRCA1 but also for other autosomal dominant disorders that are considered as being embryonically lethal.